PENDAMPINGAN INSEMINASI BUATAN DAN KESEHATAN HEWAN DI DESA SAWOJAJAR KABUPATEN LAMPUNG UTARA - REZA FAHLEVI (Pengabdian Kepada Masyarakat Cendekia, 2026)
This service activity is an effort to optimize community empowerment and contribute to providing knowledge and information through assistance with artificial insemination and animal health in Sawojajar village, North Lampung Regency. Members of the group in Sawojajar village make a living by farming and animal husbandry, with the main commodities being vegetables and cattle breeding. Due to the lack of public knowledge about animal health and artificial insemination, the community hopes for assistance from the government for a cattle breeding program that includes improving maintenance management. and the provision of superior males. This service activity is carried out through evaluation, preparation and implementation stages. Direct training, information and discussion methods are used in its implementation. The results of this service activity for the community, the majority of which are smallholder farmers, are very good, namely enthusiastic participation in this assistance until this activity is completed. Participants also asked a lot about the health of their livestock, how to deal with diseases experienced by their livestock, such as diseases from bacteria, viruses, fungi and parasites. Farmers in Sawojajar village with this service know both traditional and modern ways of handling special care management in animal health.